Status Gizi, Aktivitas Fisik, dan Asupan Cairan Dengan Status Dehidrasi Pada Petani di Kabupaten Jeneponto (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2023)
Dehydration that occurs in adults is influenced by various factors including age, gender, fluid intake, physical activity, nutritional status, body temperature and environmental temperature. This study aims to determine the relationship between nutritional status, fluid intake and physical activity with the incidence of dehydration in corn farmers in Jeneponto Regency. This research is a quantitative study using an analytic observational approach with a Cross Sectional Study design. The sample in the study was 99 respondents obtained by using the slovin formula with the Proportional Random Sampling technique based on the residence in the respondent's hamlet area. Data were analyzed using the chi-square test. To determine the risk (Odds ratio) of exposure to cases, a confidence interval (CI) value of 95% (α 0.05) was used. The results of the study showed that there was a relationship between nutritional status (p=0.000, OR=0.659), physical activity (p=0.000, OR=3.430) and fluid intake (p=0.003, OR=0.225) with dehydration status in farmers in Jeneponto District. Nutritional status, physical activity and fluid intake are risk factors associated with dehydration in corn farmers in Jeneponto Regency. Corn farmers are expected to pay more attention to daily fluid intake, by bringing drinking water facilities to the workplace and consuming drinking water at least 2 liters/day.